2010
DOI: 10.1007/s10903-010-9316-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Breast Cancer Screening Among Haitian Immigrant Women in Little Haiti, Miami

Abstract: Previous research has not examined barriers to mammography screening among Haitian immigrant women through their own discourse. Community Health Workers conducted in-depth interviews with Haitian women in Little Haiti, Miami. We used a grounded theory approach to analyze data from the in-depth interviews. Emergent themes coalesced into three core categories of screening barriers: Structural, Psychosocial, and Socio-Cultural. We developed a model of screening barriers to depict the themes within each core categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…As in the Kobetz et al [26] study of Haitian immigrants, we found that fear around diagnosis/results and fear of pain during mammography is a common barrier. Sociocultural notions of illness as symptomatic were similarly found in this refugee community.…”
Section: Discussionsupporting
confidence: 70%
“…As in the Kobetz et al [26] study of Haitian immigrants, we found that fear around diagnosis/results and fear of pain during mammography is a common barrier. Sociocultural notions of illness as symptomatic were similarly found in this refugee community.…”
Section: Discussionsupporting
confidence: 70%
“…As a result, the barriers to access to health care have been studied in several continents such as Latin America, USA, Europe, Asia and Africa, to better understand this phenomenon (10,(17)(18)(19)(20)(21)(22) . However, little is known about the barriers faced in accessing health care to breast cancer in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Underutilization of mammography screening among immigrant women has been associated with cultural beliefs, limited English proficiency, lower cancer literacy, religious beliefs, fear, lack of physician recommendation, and lack of health insurance (Carroll et al, 2007;Engelman, Cizki, Ellerbeck, & Rempusheski, 2012;Kobetz et al, 2010;Pavlish, Noor, & Brandt, 2010). Low health literacy and low cancer literacy may pose major obstacles to reading and comprehending medical information, such as prevention materials, patient intake forms, consent forms, and medical prescriptions.…”
mentioning
confidence: 99%